Determination of optimum liquidity for effective monetary policy in Nigeria - Central Bank of Nigeria, Research Department; Tule, Moses K. (Abuja, Nigeria Central Bank of Nigeria, 2015)
Investigated the optimal liquidity that facilitated effective implementation of monetary policy in Nigeria
Includes bibliographical references.
oif 1605/17
Reference
Keywords: Liquidity management; Monetary policy; Nigeria